Demographic Change and the Length of Working Life in the Region of Magellan and Chilean Antartic 1992-2013 - Rivero-Cantillano, R (UNIV MAGALLANES, 2018)
This article analyzes the implications of the demographic change in the region of Magellan and the Chilean Antarctic. It analyzes the dynamics of population aging and its impact on the labor force. In particular, it was observed the variation the working life s length through the gross and net years of economic activity, the pattern of entrance and retirement and the working life expectancy. Methodologically, we elaborated Tables of Working Life for the years 1992, 2003 and 2013. We also used information of economic activity and inactivity for the region obtained from the National Socioeconomic Characterization Survey (CASEN in spanish) and published mortality tables by National Statistics Institut (INE, 2004).